Math Playground Assisted Discovery Learning Shapes Analytical Reasoning Alongside Teamwork Outcomes: Discovery Learning Berbantuan Math Playground Membentuk Hasil Penalaran Analitis Beserta Kerja Sama - Andriani, Dia; Sulistiyo, Urip; Nugraha, Ugi (Academia Open, 2026)
General Background Modern education demands the mastery of 21st-century competencies to prepare individuals for global challenges. Specific Background Elementary mathematics instruction typically relies on teacher-centered mechanical memorization, which severely limits active participation and social interaction. Knowledge Gap Although digital platforms offer interactive opportunities, conventional teaching practices rarely integrate gamified media systematically into structured pedagogical syntax to simultaneously build cognitive and cooperative competencies. Aims This collaborative classroom action research implements the Discovery Learning model assisted by Math Playground to elevate analytical evaluation and group cooperation among 20 fourth-grade students. Results Following two structured cycles of observation and testing, analytical proficiency escalated from 67.19% to 84.38%, while cooperative capabilities surged from 67.75% to 84.25%. Novelty This study seamlessly embeds digital gameplay into the specific syntax of Discovery Learning, ensuring that virtual challenges act as core mechanisms for conceptual exploration rather than mere supplementary entertainment. Implications Practitioners must transition toward these integrated, student-centered frameworks to successfully cultivate the essential cognitive and interactive proficiencies required in contemporary academic environments. Highlights Digital gamification significantly elevates group participation during mathematics instruction. Two cycles of classroom action research demonstrate substantial gains within elementary student proficiency. Integrating interactive platforms into pedagogical syntax effectively replaces traditional teacher-centered mechanical memorization. Keywords Critical Thinking; Collaboration Skills; Mathematics Education; Classroom Action Research; Interactive Media